Development and initial validation of the Positive Sexuality Scale for female adults. Issue 7 (7th January 2019) - Casu, Giulia
Abstract: Aim and objectives: To develop and initially validate the Positive Sexuality Scale (PSS) to assess adult female‐positive sexuality. Background: While traditional approaches focus on negative sexual experiences and sexual dysfunctions, within the positive psychology framework positive sexuality is a subjective experience of happiness and fulfilment with one's sexual expression, which contributes to well‐being. No measure exists that specifically measures adult female‐positive sexuality and can be confidently used with women of any fertility/childlessness status. Design: Two‐stage cross‐sectional study with a 4‐week test–retest, which follows the STROBE guidelines. Methods: Participants were 912 Italian women aged 18–45 (52.74% mothers, 23.79% voluntarily childless and 23.46% primary infertile), who completed the 5‐item PSS and a self‐report of psychological well‐being. A subsample ( n = 61) completed the 4‐week test–retest. Results: Factor analyses supported a one‐factor model with measurement invariance across adulthood stage and fertility/childlessness status and good reliability. Younger and fertile women showed higher PSS scores, and moderate‐to‐high variability in infertile women's well‐being was accounted for by PSS scores. Conclusion: The PSS is a brief self‐report with initial evidence of validity and reliability that could be used in sex research, practice and education. Relevance to clinical practice: The PSS could assist health professionals to identify a positive resource to which women can draw on to deal with sex‐related issues. Implementing the assessment of female‐positive sexuality in infertility protocols could help professionals to identify a potential resource within couples facing infertility and its treatment.